Influence of chemical concentrations on the physicochemical, structural, functional and color characteristics of chitin isolated from Arabian red shrimp (Aristeus alcocki) - M.K. Rasweefali; A. Nayana; M.K. Raseel Rahman; H. Habeebrehman; S. Sabu (Sustainable Chemistry for the Environment)
This study examines the physicochemical, functional and structural characteristics of α-chitin extracted from the exoskeleton of Arabian red shrimp using varying concentrations of HCl and NaOH. By employing HCl and NaOH at concentrations of 0.6, 1.0 and 1.4 M, this study systematically evaluates the degree of acetylation (DA), molecular weight (Mw), whiteness, purity, crystallinity, and other key parameters of the isolated chitin samples in comparison to commercial chitin (CCN). Results indicate a varied range of N-acetyl group content (77.34 ± 1.13 % to 96.56 ± 1.18 %) and crystallinity values (36.40–44.20 %) across different acid and alkali concentration combinations. This study highlights the effectiveness of deproteinization and demineralization processes in most cases, as confirmed by EDS microanalysis, which demonstrated the complete removal of minerals. Morphological analysis using FE-SEM revealed a smooth, porous and microfibrillar structure in the isolated chitin samples. The study emphasizes the significant influence of the extraction process on chitin properties, with lower concentrations of HCl and NaOH yielding higher CrI and DA. Furthermore, increased concentrations of HCl and NaOH were associated with decreased Mw and increased fat-binding capacity (FBC) and water-binding capacity (WBC) of the isolated chitin samples. This study enhances understanding of how species-specific traits and processing conditions influence chitin characteristics, enabling researchers to predict and select crustacean species for chitin isolation based on desired functional properties.